PEMETAAN WILAYAH SEKTOR UNGGULAN DI RPOVINSI JAWA TIMUR MELALUI ANALISIS INPUT-OUTPUT TAHUN 2013 - Kyswantoro, Yunita Firdha (Jurnal Ilmiah Mahasiswa FEB, 2016)
The results of the determination of the leading sectors using table I-O 2013 analysis in East Java Province can give an idea of what the development sector has the potential to increase economic growth in the relevant area. There also happend some incompability between spatially and the situation leading sector in a region. Some areas that produce the leading sectors sometimes have low accessibility to the sector both input and output sectors. After recognizing the leading sectors in East Java Province, this will be expected to know also the growth pole area that improve society welfare. With several analytical methods have been determined, the study aims to: (1) determine what activities are becoming leading sector in East Java province 2013, (2) determine which area is belonging to the leading sectors in the East Java Province, (3) determine how the relationship between the growth pole area with the level of accessibility to the region that has the leading sectors in Â East Java. The place and time of this study are in all districts and cities in East Java during 2013. The ana lytical method to be used is the method of analysis I-O updating tables 2013, structural mapping, and mapping the distribution of leading sectors in the region. The results showed that there were 17 leading sectors in East Java Province, based on the results of mapping the distribution of leading sector in the region are Gresik-Surabaya- Sidoarjo in accordance with the Growth Pole Theory and principle of cost minimization Weber.Keywords: Leading Sector, I-O Analysis, Mapping of the Distribution Territory